MRI Abnormalities After Prolonged Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The clinical, radiologic, and laboratory findings of 17 Asian patients with encephalopathy following a prolonged febrile seizure were reviewed retrospectively at Kameda Medical Center, and other centers in Japan and San Francisco, USA.